Meprin Metalloprotease Deficiency Associated with Higher Mortality Rates and More Severe Diabetic Kidney Injury in Mice with STZ-Induced Type 1 Diabetes - John E. Bylander; Faihaa Ahmed; Sabena M. Conley; Jean-Marie Mwiza; Elimelda Moige Ongeri (Journal of Diabetes Research)
Meprins are membrane-bound and secreted metalloproteinases consisting of α and/or β subunits that are highly expressed in kidney epithelial cells and are differentially expressed in podocytes and leukocytes (macrophages and monocytes). Several studies have implicated meprins in the progression of diabetic nephropathy (DN) and fibrosis-associated kidney disease. However, the mechanisms by which meprins modulate DN are not understood. To delineate the role of meprins in DN, we subjected meprin αβ knockout (αβKO) mice and their wild-type (WT) counterparts to streptozotocin-induced type 1 diabetes. The 18-week survival rates were significantly lower for diabetic meprin αβKO mice when compared to those for their WT counterparts. There were significant decreases in mRNA and protein levels for both meprin α and β in diabetic WT kidneys. Furthermore, the blood urea nitrogen levels and urine albumin/creatinine ratios increased in diabetic meprin αβKO but not in diabetic WT mice, indicating that meprins may be protective against diabetic kidney injury. The brush border membrane levels of villin, a meprin target, significantly decreased in diabetic WT but not in diabetic meprin αβKO kidneys. In contrast, isoform-specific increases in cytosolic levels of the catalytic subunit of PKA, another meprin target, were demonstrated for both WT and meprin αβKO kidneys.